Cerebral perfusion in chronic fatigue syndrome and depression. - MacHale, S; Lawŕie, S; Cavanagh, J; Glabus, M; Murray, C; Goodwin, G; Ebmeier, K (2000)
BACKGROUND: Patients with chronic fatigue syndrome (CFS) and depressive illness share many, but not all, features. AIMS: To test the hypothesis that patients with CFS have abnormal cerebral perfusion, that differs from that in patients with depressive illness. METHOD: We recruited 30 patients with CFS who were not depressed, 12 depressed patients and 15 healthy volunteers. Regional cerebral perfusion at rest was assessed using region of interest (ROI) and voxel-based statistical parametric mapping (SPM) techniques. RESULTS: On SPM analysis there was increased perfusion in the right thalamus, pallidum and putamen in patients with CFS and in those with depressive illness. CFS patients also had increased perfusion in the left thalamus. Depressed patients differed from those with CFS in having relatively less perfusion of the left prefrontal cortex. The results were similar on ROI analysis. CONCLUSIONS: Abnormal cerebral perfusion patterns in CFS subjects who are not depressed are similar but not identical to those in patients with depressive illness. Thalamic overactivity may be a correlate of increased attention to activity in CFS and depression; reduced prefrontal perfusion in depression may be associated with the greater neuropsychological deficits in that disorder.